The future of work and environmental sustainability: Balancing automation and green jobs - Yahya Majeed Alsaad; Bushra Jabbar Abdul Kareem; Zina Muin Mohammed; Dhafer Aldabagh; Thamer Kadum Yousif Al Hilfi; Larysa Prots (Environment and Social Psychology, 2025)
The rate at which automation has swept the world, does not only capture the attention of a number of emerging industries and revolutionizing productivity schemes but also defying concepts toward environmental sustainability and labor allocation. Although automation is typically linked to an increase in productivity and competitive advantage, the greater opportunity of automation in the rate of energy consumed and the emissions reduction and green jobs creation remain not sufficiently measured. The paper discusses how automation is producing two impacts, which have implications on the future of both production and the labor markets, in manufacturing and logistics and agriculture and retail sales. By employing a mixed-method analysis methodology, longitudinal data analysis was supplemented with econometric modelling, to determine the impacts of automation on the energy efficiency trends (carbon reduction and employment). Regression test, sensitivity and validation tests were performed in order to support both the sector level case studies and the robustness of empirical estimates to ascertain that the results are empirically strong. The outcomes of automation, according to the results, reduce energy consumption (18-25 percent) and greenhouse gases (15-20 percent) in major uptake areas such as manufacturing and logistics. Meanwhile, green job creation increased by a factor of 15-28% with a particular growth in middle and high-skilled jobs. Horticulture and retail were slower but had less significant sustainability benefits, confirming the disproportionate spread of automation technology in sectors. Nevertheless, under adaptive policies, upskilling of the labor force and incorporation of green technologies turn out to be environmental and social opportunities in the decarbonization and inclusive growth of countries. The findings imply that a sector-specific governance strategy and long-term oversight will be required to make a balanced sustainability change to produce an equalized transition to the low-carbon automated economy.